2022
DOI: 10.1042/cs20220149
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and syncytiotrophoblast membrane extracellular vesicles (STB-EVs)

Abstract: Preeclampsia (PE) is a hypertensive complication of pregnancy that affects 2–8% of women worldwide and is one of the leading causes of maternal deaths and premature birth. PE can occur early in pregnancy (<34 weeks gestation) or late in pregnancy (>34 weeks gestation). Whilst the placenta is clearly implicated in early onset PE (EOPE), late onset PE (LOPE) is less clear with some believing the disease is entirely maternal whilst others believe that there is an interplay between maternal systems a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 106 publications
0
19
0
Order By: Relevance
“…During the late stages of pregnancy, syncytiotrophoblast (STB)-EVs are released directly into the maternal circulation and can be uniquely recognized by a placental alkaline phosphatase [ 83 ]. STB-EVs have been shown to carry several proteins including endoglin, plasminogen activator inhibitor, soluble fms-like kinase (sFlt), and endothelial nitric oxide synthase [ 84 , 85 ], as well as miRNAs [ 86 , 87 ], tRNA [ 88 ], and DNA [ 81 , 89 ]. The physiological functions of peripherally circulating STB-EVs in both in vitro and in vivo investigations are broad and their molecular contents as well as surface markers are powerful and cannot be underestimated.…”
Section: Biology Of Extracellular Vesiclesmentioning
confidence: 99%
“…During the late stages of pregnancy, syncytiotrophoblast (STB)-EVs are released directly into the maternal circulation and can be uniquely recognized by a placental alkaline phosphatase [ 83 ]. STB-EVs have been shown to carry several proteins including endoglin, plasminogen activator inhibitor, soluble fms-like kinase (sFlt), and endothelial nitric oxide synthase [ 84 , 85 ], as well as miRNAs [ 86 , 87 ], tRNA [ 88 ], and DNA [ 81 , 89 ]. The physiological functions of peripherally circulating STB-EVs in both in vitro and in vivo investigations are broad and their molecular contents as well as surface markers are powerful and cannot be underestimated.…”
Section: Biology Of Extracellular Vesiclesmentioning
confidence: 99%
“…In contrast, Wei et al explored the role of placenta debris in PE and discovered that PE placenta debris contains a microRNA profile different from that of normal pregnancy ( 13 ). Their EVs were generated with placental explants, a less physiological model than ex-vivo dual lobe perfusion ( 14 ). However, the small RNA composition of the EVs from the explant culture differs from that derived from the ex-vivo dual lobe perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the molecular mechanisms underlying the effect of circulating factors remain to be further explored. As evidenced by the increasing number of publications on placental extracellular vesicles (pEVs) which are present in the maternal circulation detected as early as at 6 weeks of gestation, they have been built to link the pathogenesis of pregnancy disorders, especially PE [ 7 ]. EVs are categorized as microvesicles (MVs), exosomes (Exos) and apoptotic bodies (Abs), based on their size and biogenic pathway [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MISEV (minimum information for the study of extracellular vesicles) guideline have recommended that physical characteristics, such as size, are used for classify EVs without biogenic synthesis evidence[ 9 ]. In general, EVs have defined as small EVs (sEVs) with size < 220 nm and medium/large EVs (m/lEVs) with size ≥ 220 nm [ 7 ]. Mounting studies have revealed that pEVs markedly elevated in PE patient are engaged in endothelial dysfunction, imbalanced angiogenesis and systemic inflammation, all of which eventually aggravate the disease development [ 10 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation